Well...... I'm confused too but I'll go with:
Simplifying
X2 + 8x + -55 = 10
Reorder the terms:
-55 + X2 + 8x = 10
Solving
-55 + X2 + 8x = 10
Solving for variable 'X'.
Move all terms containing X to the left, all other terms to the right.
Add '55' to each side of the equation.
-55 + X2 + 55 + 8x = 10 + 55
Reorder the terms:
-55 + 55 + X2 + 8x = 10 + 55
Combine like terms: -55 + 55 = 0
0 + X2 + 8x = 10 + 55
X2 + 8x = 10 + 55
Combine like terms: 10 + 55 = 65
X2 + 8x = 65
Add '-8x' to each side of the equation.
X2 + 8x + -8x = 65 + -8x
Combine like terms: 8x + -8x = 0
X2 + 0 = 65 + -8x
X2 = 65 + -8x
Simplifying
X2 = 65 + -8x
Reorder the terms:
-65 + X2 + 8x = 65 + -8x + -65 + 8x
Reorder the terms:
-65 + X2 + 8x = 65 + -65 + -8x + 8x
Combine like terms: 65 + -65 = 0
-65 + X2 + 8x = 0 + -8x + 8x
-65 + X2 + 8x = -8x + 8x
Combine like terms: -8x + 8x = 0
-65 + X2 + 8x = 0
-Hope this helps!!